Echocardiographic screening for the anomalous aortic origin of coronary arteries - Francesco Bianco; Valentina Bucciarelli; Sabina Gallina; Massimo Colaneri; Francesca Chiara Surace; Federica Valentina Iezzi; Martina Primavera; Annaclara Biasi; Giuliano Giusti; Emanuela Berton; Monica Baldoni; Giulia Renda; et al. (Open Heart)
Aims We sought to determine the diagnostic performance, clinical profiles and outcomes of anomalous aortic origin of coronary arteries (AAOCA) using a standardised echocardiographic approach in young adults and athletes.Methods In 2015–2019, we screened 5998 outpatients (age 16 years (Q1–Q3: 11, 36)), referred for routine echocardiography, using four specific echocardiographic windows: parasternal short/long axis and apical 4/5-chambers view. Coronary CT confirmed AAOCA. For the performance analysis, 300 coronary-CT scans were available; two independent and double-blinded physicians retrospectively reviewed echocardiographic images.Results A total of 47 AAOCA was diagnosed; the overall prevalence was 0.0078%. Over 5 years, we found a significant increment of AAOCA diagnostic rate (P for trend=0.002). Syncope (n=17/47) and palpitations (n=6/47) were prevalent symptoms. All patients suspended sports activity at the diagnosis. Twenty-seven patients underwent surgery, while 20 underwent a conservative medical treatment. All patients are alive at a median follow-up of 3±1.6 years; only surgical repairs restarted their activity. Our method showed better sensitivity than traditional short-axis evaluation: 93% vs 83%, p=0.0030 (AUC 0.96 (95% CI 0.92, 0.99) and AUC 0.89 (95% CI 0.83, 0.95), respectively), with a good interobserver agreement (95%, k=0.83, p<0.001).Conclusions The application of a standardised echocardiographic approach for AAOCA detection led to a significantly increased rate of identified anomalies. This approach demonstrated higher sensitivity than the traditional echocardiographic assessment. Implementing this protocol in clinical practice may help improve the AAOCA diagnosis in young adults and athletes.Trial registration number NCT04224090.